Evaluasi pembelajaran daring di pgsd pada era pandemi covid 19 ditinjau dari pelaksanaa asesmen - Poerwanti, Jenny Indrastoeti Siti; Marmoah, Sri (Jurnal Pendidikan Dasar, 2024)
The impact of the Covid-19 pandemic has affected learning activities at both the primary and higher education levels. Learning which was initially carried out directly in the classroom turned to learning using online media and was carried out virtually using the internet network. This study aims to (1) evaluate the implementation of online learning assessments, (2) describe the obstacles encountered in the implementation of online assessments. The research used a qualitative research approach with descriptive type. The subjects of this study were PGSD FKIP UNS students in even semesters. The data collection techniques used were questionnaires, observations and documents. The credibility of this research data was achieved through triangulation. The data collection technique is done by using an interactive model. The output of this research is a national journal with ISSN. The results of the study concluded that (1) the online assessment carried out in the UNS PGSD study program during the Covid-19 pandemic, had used various platforms and used various forms of assessment or assessment in accordance with the designed learning plan and had fulfilled the assessment steps. (2) the assessment platform applied in the online learning process includes online-based assessment, using Spada, Gmail, WA. The forms of assessment used are written tests, assignments, and presentations. (3) The obstacles faced are the use of the Spada menu has not been maximally used, the internet network is less stable, the preparation of an authentic online assessment requires planning..